Monitoring and evaluation of water quality in rural Andean areas of Peru using wireless sensors with LoRa - Wohler GONZALES SAENZ; Luz Marina ACHARTE LUME; Javier Camilo POMA PALACIOS; Alejandro Filimón QUISPE COICA; Agustí PÉREZ FOGUET (ITEGAM-JETIA)
The objective of this research was to implement wireless sensors for remote monitoring and evaluation of water quality in five reservoirs in rural Andean communities in the district of Huancavelica-Peru, given the scarcity of information on water quality and its poor monitoring. It is important to monitor water quality for its safe management according to the sustainable development goals of the 2030 agenda, against natural or anthropogenic contaminants. The remote monitoring evaluated the performance of wireless sensors and water quality (temperature, pH and turbidity) for 10 days. The wireless sensors were calibrated with Hanna Instruments brand equipment achieving an R² of 98.98%, 96.81% and 89.82% for temperature, pH and turbidity respectively. The average amount of data received was 456/462, 8.73 km maximum communication distance, received signal strength RSSI (-93 to -122 dBm), signal to noise ratio SNR (9 to 13 dB), water temperature (-2.90 to 14.4 ºC), pH (6.60 to 8.24) and turbidity (0.34 to 4.98 NTU). The wireless sensors are highly effective in remote monitoring; the quality of the monitored water complies with Peruvian and World Health Organization regulations.